The c-sis gene encodes a precursor of the B chain of platelet-derived growth factor. - Johnsson, A (1984)
The relationship between platelet-derived growth factor (PDGF) and the proto-oncogene c-sis has been determined by amino acid sequence analysis of PDGF and nucleotide sequence analysis of c-sis genomic clones. The nucleotide sequences of five regions of the human c-sis gene which are homologous to sequences of the transforming region (v-sis) of simian sarcoma virus (SSV) were determined. By alignment of the c-sis and v-sis nucleotide sequences the predicted amino acid sequence of a polypeptide homologous to the putative transforming protein p28sis of SSV was deduced. Both predicted sequences use the same termination codon and additional coding sequences may lie 5' to the homologous regions. Amino acid sequence analysis of the PDGF B chain shows identity to the amino acid sequence predicted from the c-sis sequences over 109 amino acid residues. Polymorphism may exist at two amino acid residues. These results suggest that c-sis encodes a polypeptide precursor of the B chain. A partial amino acid sequence of the PDGF A chain is also described. This chain is 60% homologous to the B chain and cannot be encoded by that part of c-sis which has been sequenced but could be encoded by sequences which lie 5' to the five regions of v-sis homology in c-sis, or at a separate locus.